Assessing the Role of Immigration in the Linkage Between School Safety, Education, and Juvenile Justice Contact, Texas, 2000-2019 - Marchbanks III, Miner P. ([Verlag nicht ermittelbar], 2022)
This project utilizes secondary data analysis of existing data. Recognizing that the school discipline and juvenile justice experience of immigrants may differ from non-immigrant children, the project explores the role immigration status and border location has on these outcomes.